2007
DOI: 10.1051/0004-6361:20077915
|View full text |Cite
|
Sign up to set email alerts
|

Spots, plages, and flares onλAndromedae and II Pegasi

Abstract: Aims. We present the results of a contemporaneous photometric and spectroscopic monitoring of two RS CVn binaries, namely λ And and II Peg. The aim of this work is to investigate the behavior of surface inhomogeneities in the atmospheres of the active components of these systems that have nearly the same temperatures but different gravities. Methods. The light curves and the modulation of the surface temperature, as recovered from line-depth ratios (LDRs), were used to map the photospheric spots, while the Hα … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
156
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(173 citation statements)
references
References 54 publications
15
156
2
Order By: Relevance
“…As seen in Table 5, for the three stars with fairly long rotation periods (#10, #14, and #17) ΔT is in the range 1000-1300 K, i.e. smaller than sunspot umbrae but slightly larger than values of 400-900 K found for the giant and sub-giant components of RS CVn binaries adopting a similar approach (Frasca et al 2005(Frasca et al , 2008. Conversely, the spotted area (8-10% of the star surface) is smaller, on average, than that found by Frasca et al (2005Frasca et al ( , 2008 for RS CVn stars (A rel = 11-18%).…”
Section: Spot Propertiesmentioning
confidence: 81%
“…As seen in Table 5, for the three stars with fairly long rotation periods (#10, #14, and #17) ΔT is in the range 1000-1300 K, i.e. smaller than sunspot umbrae but slightly larger than values of 400-900 K found for the giant and sub-giant components of RS CVn binaries adopting a similar approach (Frasca et al 2005(Frasca et al , 2008. Conversely, the spotted area (8-10% of the star surface) is smaller, on average, than that found by Frasca et al (2005Frasca et al ( , 2008 for RS CVn stars (A rel = 11-18%).…”
Section: Spot Propertiesmentioning
confidence: 81%
“…This fair coherence confirms the hypothesis of cool spots as the primary cause of the observed variations. The temperature varies between 5162 K and 5249 K, with a full amplitude of about 90 K, which is intermediate between the values of ≈40 K found in moderately active stars (Biazzo et al 2007b) and ≈130 K found in highly active stars (Catalano et al 2002;Frasca et al 2005Frasca et al , 2008a.…”
Section: Effective Temperature From Line-depth Ratiosmentioning
confidence: 98%
“…Our main aim is the determination of the spot temperature and filling factor and to infer the distribution of chromospheric ARs of SAO 51891. The general scope is the comparison of the results obtained for very young stars, such as SAO 51891, with those found for MS and RS CVn stars (see, e.g., Frasca et al 2005Frasca et al , 2008aBiazzo et al 2007b). …”
Section: Article Published By Edp Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main aims of the young cluster observations is to study their kinematics and dynamical evolution through the measurement of accurate radial velocities . The high-quality of GIRAFFE and UVES spectra also allows us to study their metallicities and elemental abundances, rotational velocities, chromospheric activity, and accretion rates (e.g., Spina et al 2014;Frasca et al 2015). So far, the dynamical properties of several young clusters have already been observed and analyzed.…”
Section: Introductionmentioning
confidence: 99%